Ethnography of Child Labor in Paotere City of Makassar - Jafar N, Muhammad Kamil (Department of Anthropology, 2023)
This article uses ethnographic research method to analyze the phenomenon of child labor in Paotere. It discusses history and culture of children working in Paotere. The family environment of child laborers also influenced them to work to have secondary income earners for the family. Data collection was conducted for one year from January to December 2021. This research uses four stages: firstly identification, data collection, data reduction and directional discussion. Data collection includes observation, in-depth interviews, and group discussions. Dialogue between exploitation and culture retained by child laborers is discoursed specifically in this article.Abstrak: Artikel ini menggunakan metode penelitian etnografi untuk menganalisis fenomena pekerja anak di Paotere. Ini membahas sejarah dan budaya anak-anak yang bekerja di Paotere. Lingkungan keluarga pekerja anak juga mempengaruhi mereka untuk bekerja mencari nafkah sampingan bagi keluarga. Pengumpulan data dilakukan selama satu tahun dari Januari hingga Desember 2021. Penelitian ini menggunakan empat tahapan yaitu identifikasi, pengumpulan data, reduksi data dan pembahasan terarah. Pengumpulan data meliputi observasi, wawancara mendalam, dan diskusi kelompok. Dialog antara eksploitasi dan budaya yang dipertahankan oleh pekerja anak diwacanakan secara khusus dalam artikel ini.